Decadal observations of global daytime cloud properties from DSCOVR–EPIC - Yang, Yuekui; Bhatta, Surendra; Delgado-Bonal, Alfonso (Frontiers in Remote Sensing, 2025)
This study presents a decadal analysis of global daytime cloud properties using observations from the Earth Polychromatic Imaging Camera (EPIC) aboard the Deep Space Climate Observatory (DSCOVR) satellite from July 2015 to December 2024. We focus on cloud fraction and cloud effective height (CEH) from the EPIC standard Level-2 (L2) cloud products. Consistent with other satellite observations, the EPIC-derived decadal global cloud fraction shows high cloudiness over tropical convergence zones and midlatitude storm tracks and reduced cloud cover over subtropical regions associated with the descending branches of the Hadley circulation. Seasonal analysis shows greater variability over land, while cloud fraction remains consistently higher over oceans. Trend analysis using the Mann–Kendall and Theil–Sen methods identifies a statistically significant decreasing trend in the cloud fraction over land (−0.0329 per decade, p = 0.014), primarily confined to the Northern Hemisphere. No significant trend is found over ocean or in the CEH. Spatial trend maps highlight that the regional cloud fraction decreases over the western tropical Pacific and central Africa and increases over parts of the midlatitude oceans. These results demonstrate EPIC’s capability in tracking global and regional cloud variability and contribute to our understanding of cloud–climate interactions.